Stock Market Declines and Liquidity - HAMEED, ALLAUDEEN; KANG, WENJIN; VISWANATHAN, S. (Journal of Finance, 2010)
ABSTRACT Consistent with recent theoretical models where binding capital constraints lead to sudden liquidity dry‐ups, we find that negative market returns decrease stock liquidity, especially during times of tightness in the funding market. The asymmetric effect of changes in aggregate asset values on liquidity and commonality in liquidity cannot be fully explained by changes in demand for liquidity or volatility effects. We document interindustry spillover effects in liquidity, which are likely to arise from capital constraints in the market making sector. We also find economically significant returns to supplying liquidity following periods of large drops in market valuations.